Sistema de apoio à decisão baseado em ontologia de domínio nutricional para monitoramento da disfagia - Sousa, José Carlos Marinheiro de (Universidade Federal Rural do Semi-Árido, 2019)
Information and communication technology (ICT) can play a key role in improving health care for individuals and communities. By providing more efficient ways to access, communicate and store information. Through the development of databases and other applications, ICT also provides the ability to improve health system efficiency to prevent medical errors. Therefore, this research aims to develop a module of a system to assist the treatment and diagnosis of oropharyngeal dysphagia. Characterized by the difficulty of eating food, oropharyngeal dysphagia is not a simple dysfunction, demanding the action of a multidisciplinary team, for example, the speech therapist and nutritionist. Nutritional treatment and oral mobility activities are essential for the improvement of the dysphagic patient and for the transition from enteral to oral diet. The proposed module will consist of a web application and the use of application ontologies. The effective contribution of this work is to expand a system through a module that facilitates relating dysphagia in different professional areas, helping the rehabilitation of patients with dysphagia to feed orally, and restoring their appropriate nutritional status.
Monografia
Keywords: Ontologias; Disfagia; Ingestão de alimentos; Ontologies; Dysphagia; Food intake; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO::SISTEMAS DE INFORMACAO